2009
DOI: 10.1007/s11274-009-0095-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of alkaline feruloyl esterases from Aspergillus niger CFR 1105 grown on wheat bran

Abstract: Feruloyl esterases (FAEs) of a strain of Aspergillus niger (CFR 1105) grown in solid state (ssf) and submerged fermentations (smf) using wheat bran both as carbon source and inducer of the enzyme were studied. The feruloyl esterase activity was maximum after 4 days in solid state as well as in submerged fermentations (32.5 and 31.5 U/g dry weight of wheat bran respectively) and the enzyme titers were comparable. The specific activity was maximum on day 2 in ssf (12.8 U/mg protein) and it decreased thereafter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 31 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…It is much higher than that of FAE-1 from Aspergillus niger (9.0 8 0.1 U/mg) [Hedge and Muralikrishna, 2009], FAE-2 from A. niger (11.2 8 0.02 U/mg) [Hedge and Muralikrishna, 2009] and FAE from Eleusine coracana (3.375 U/mg) [Latha et al, 2007]. As shown in table 1 , EstF27 displayed activity against -nitrophenyl acetate (C2), -nitrophenyl butyrate (C4), -nitrophenyl octanoate (C8) and -nitrophenyl decanoate (C10).…”
Section: Enzymatic Characterizationmentioning
confidence: 68%
See 1 more Smart Citation
“…It is much higher than that of FAE-1 from Aspergillus niger (9.0 8 0.1 U/mg) [Hedge and Muralikrishna, 2009], FAE-2 from A. niger (11.2 8 0.02 U/mg) [Hedge and Muralikrishna, 2009] and FAE from Eleusine coracana (3.375 U/mg) [Latha et al, 2007]. As shown in table 1 , EstF27 displayed activity against -nitrophenyl acetate (C2), -nitrophenyl butyrate (C4), -nitrophenyl octanoate (C8) and -nitrophenyl decanoate (C10).…”
Section: Enzymatic Characterizationmentioning
confidence: 68%
“…To date, more than 30 FAEs have been purified and characterized from fungi [Donaghy and McKay, 1997;Hedge and Muralikrishna, 2009;Koseki et al, 2009;MacKenzie and Bilous, 1988;McCrae et al, 1994;Topakas et al, 2003Topakas et al, , 2005 and bacteria [Abokitse et al, 2010;Aurilia et al, 2007;Dalrymple et al, 1996;Donaghy et al, 2000;Faulds and Williamson, 1991;Lai et al, 2009;Mukherjee et al, 2007;Rashamuse et al, 2007;Wang et al, 2004]. However, more than 99% microorganisms in the environment cannot be cultured using conventional methods [Amann et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, family VIII esterases are typically tested for their ability to hydrolyse a variety of β-lactam substrates ( Table 2). The majority either lack the activity or show negligible activity, despite the high sequence identity to the β-lactamases, while others have been described as exhibiting "promiscuous β-lactamase activity" [18,21,41,47,48,49]. Consequently, it has been suggested that these esterases have evolved from the class C β-lactamases, where some have maintained this remnant activity, while others have lost the capability due to steric interference resulting from structural evolution [18,41,50].…”
Section: Discussionmentioning
confidence: 99%
“…The specific activity of EstF27 towards p-nitrophenyl ferulate was 21.7 AE 1.7 U mg À1 , which is much higher than those of other FAEs (3.375 U mg À1 for FAE from Eleusine coracana, 9.0 AE 0.1 U mg À1 for FAE-1 from Aspergillus niger and 11.2 AE 0.02 U mg À1 for FAE-2 from A. niger; Latha et al, 2007;Hegde & Muralikrishna, 2009). EstF27 also exhibits several novel features, including halotolerance (retaining more than 50% activity after 96 or 120 h incubation in the presence of 3 M KCl or 5 M NaCl), alkali tolerance (being stable over the relatively large pH range 5-10) and highly soluble expression in Escherichia coli.…”
Section: Introductionmentioning
confidence: 86%